GADD45B Is a Potential Diagnostic and Therapeutic Target Gene in Chemotherapy-Resistant Prostate Cancer - Wang, Qiong; Wu, Wanhua; Gao, Ze; Li, Kaiwen; Peng, Shirong; Fan, Huiyang; Xie, Zhongqiu; Guo, Zhenghui; Huang, Hai (Frontiers in Cell and Developmental Biology, 2021)
Background: Chemo-resistance is the major cause of death in advanced prostate cancer (PCa), especially in metastatic PCa (mPCa). However, the molecular mechanisms underlying the chemo-resistance of PCa remain unclear. Understanding the reason behind the drug resistance would be helpful in developing new treatment approaches. Methods: The TCGA, GEO datasets and clinical samples were used to examine the correlation between GADD45B with clinical characteristics and prognosis. Lentiviral transfection was used to construct GADD45B overexpression cell lines. Hypoxic incubator, low serum medium or docetaxel was used to build environmental stress model or chemotherapy cell model. The MTS assay and colony formation assay were used to test cell viability. Apoptosis and cell cycle were detected by flow cytometry. The RNA and protein levels of related biomarkers were tested by WB and qPCR. Bioinformatics analysis after RNA sequencing was performed to identify the possible mechanism of how GADD45B regulates chemotherapy resistance. Results: GADD45B was related to distant metastasis but not to Gleason score, PSA level, T stage or lymph node metastasis, and indicated a good prognosis. The level of GADD45B increased significantly in PCa cells that faced environmental stress. It was found that high level of GADD45B significantly enhanced the chemo-sensitivity. Furthermore, high GADD45B promoted cell apoptosis via MAPK pathway. Conclusions: GADD45B promoted chemo-sensitivity of prostate cancer through MAPK pathway. GADD45B could serve as a diagnostic biomarker and therapeutic target for mPCa or chemotherapy resistant patients.